KARAKTERISASI ENAM VARIETAS BUNCIS (Phaseolus vulgaris L.) BERDASARKAN PANDUAN PENGUJIAN INDIVIDUAL - Vina Eka Aristya; Intan Gilang Cempaka (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2013)
Beans (Phaseolus vulgaris L.) is a plant that has the potential for mainstream consumers, have a large enough market opportunity and a source of vegetable protein. “Perancis” varieties are local Central Java bean varieties are widely grown in the Bandungan area. “Perancis” varieties not currently provide enough characters clear and complete. Test objectives were (1) to characterize the “Perancis” varieties in order to have a complete character information varieties and (2) to determine distinctness, uniformity and stability of the “Perancis” varieties compared with varieties Gypsie, Spectacular, Balitsa 1, Balitsa 2 and PV 072 using guidelines for the conduct of test for distinctness, uniformity and stability reference beans. Implemented on the Garden Seed Testing Bandungan Horticulture, Central Java with an altitude of 560-800 meters above sea level the place. Materials testing consists of six varieties of beans are “Perancis” varieties and the varieties used for comparison Gypsie, Spectacular, Balitsa 1, Balitsa 2 and PV 072. This research used a randomized block design six varieties of beans are planted side by side on three experimental plots as replications. Parameters observed include 49 characters corresponding guidelines bean plants are divided into the plant character, leaves character, flower character, pods character and seed character. Test results based guidelines, “Perancis” varieties showed eight unique characters compared to varieties of Gypsie, Spectacular, Balitsa 1, Balitsa 2 and PV 072 ie. plant height, leaf color, leaf rugosity, long (including beak) pods, the degree of the pods curvature, the shape of distal part (excluding beak) pods, length of beak pods and curvature of beak pods and “Perancis” varieties have uniformity and stability.